Lincoln vs. Davis : the war of the presidents - Hamilton, Nigel (Little, Brown and Company, 2024)
"From the New York Times bestselling presidential biographer comes the greatest untold story of the Civil War: how two American presidents faced off as the fate of the nation hung in the balance--and how Abraham Lincoln came to embrace emancipation as the last, best chance to save the Union"--